Carambolaside W Inhibited H1N1 Influenza Virus-Induced Oxidative Stress through STAT-3/BCL-XL Signaling Pathway - Jingyao Su; Jia Lai; Jiali Li; Xia Liu; Haitian Chen; Chuqing Li; Bing Zhu; Xuchao Jia; Yinghua Li (Viruses, 2023)
The H1N1 influenza virus is highly infectious and pathogenic, and in recent years, it has often presented seasonal mass outbreaks of infection. People infected with H1N1 will develop a high fever and other respiratory infection symptoms. If not treated in time, complications such as pneumonia may occur. In this study, we focused on developing drugs that can effectively fight against with H1N1 virus. A flavonoid glycoside was extracted from the carambola, then characterized by HR-ESI-MS with the molecular formula C47H58O2, and named carambolaside W. The flavonoid glycosides were found to have good anti-H1N1 influenza virus effects. In this study, we verified that carambolaside W has low toxicity and can effectively inhibit influenza virus replication in vitro. H1N1 virus infection induces intracellular oxidative stress damage to accelerate disease progression. The results showed that carambolaside W effectively inhibited the oxidative stress caused by H1N1 infection. The Western blot assay also revealed that carambolaside W alters the expression of apoptosis-related proteins in vitro and exerts a good anti-H1N1 influenza virus effect. In summary, carambolaside W is a low-toxicity natural flavonoid that can effectively treat the H1N1 influenza virus as a potential anti-H1N1 virus agent.